Investigation Of The Crime Of Embezzlement In Property - Oliestha Ageng Wicaksana; Umar Ma'ruf (Jurnal Daulat Hukum, 2020)
The purpose of this research to find out and analyze the process of investigating criminal acts of embezzlement in positions in the Ciamis Police jurisdiction, obstacles in the process of investigating criminal acts of embezzlement in positions in the Ciamis Police jurisdiction, and analyzing solutions in overcoming obstacles in the process of investigating criminal acts of embezzlement in positions in the region the law of the Ciamis PoliceThis study uses an empirical juridical approach with descriptive analysis research specifications. The data used are primary data and secondary data obtained through interviews and literature study. The data analysis method used was qualitative analysis. Furthermore, based on the results of the research, it can be concluded: Investigations on suspects of embezzlement in positions in the Ciamis Police jurisdiction with Police Report case Number: LP / 74 / B / III / 2019 / JBR / SPKT Res Ciamis, March 30, 2019 on behalf of the reporter OHT Bin JA, namely as follows: Crime Scene Examination, Investigation, Preparation of Minutes, Examination of evidence: Search, confiscation, Expert statements, arrest or detention and examination of suspects, Resume and submission of files Obstacles: not everyone knows, hearing of a criminal act of embezzlement who wants to report to the legal apparatus (police), there is collusion of a neat series of cooperation from top to bottom in the criminal act of embezzlement in a position so that it is difficult to find and because of the shrewdness of the accused or the embezzler in the position itself, the cleverness of the perpetrator criminal embezzlement in a position to cover up his crimes, especially with the advancement of technology today. Solutions in overcoming obstacles in the process of investigating criminal acts of embezzlement in positions within the jurisdiction of the Ciamis Police: Investigators must provide a sense of security if there are people who know of criminal acts of embezzlement in their positions in the jurisdiction of the Ciamis Police.Keywords: Investigation; Crime; Embezzlement.